Facile Creating a Hierarchical and Hydrophobic Fe-Co/LZSM-5 Catalyst for the Oxidative Desulfurization Process - Adhani, Lisa; Susanto, Bambang Heru; Nasikin, Mohammad (Universitas Gadjah Mada, 2024)
This research involved top-down dealumination and steam treatment methods to design the hierarchical pores of ZSM-5, which is then wet-impregnated with a Fe-Co. This method overcomes the steric barrier that hinders the oxidative desulfurization (ODS) process and makes the catalyst hydrophobic, thereby allowing it to overcome the biphasic hindrance caused by the difference in polarity between the fuel oil and the oxidant. Characterization of the catalyst's properties based on BET and BJH, XRF, and contact angle, as well as testing its performance on DBT model oil in n-hexadecane and Indonesian commercial diesel were conducted. Simulation of the reaction energy profile using density functional theory calculations was also carried out to deepen insight into the mechanism of the reaction. Results of this study show that the catalyst has excellent catalytic reactivity in the long-chain hydrocarbon ODS process, with a TOF number of 183 h−1.